Synthesis and Identification of Some Shiff Base and Chalcone Compounds and Studying the Effectiveness as Flame Retardant of Some Thermosetting Polymers - Sabrean Farhan Jawad (Journal of Global Pharma Technology, 2018)
In this work, seven additives were used, namely: (5-(6-methylbenzothiazol-2-yl)diazenyl)-2-hydroxybenzaldehyde)(AdditiveI),(5-6-methylbenzothiazol-2-yl)diazenyl)-2-hydroxyphenyl)-1-(4-hydroxy-3-methoxyphenyl)prop-2-en-1-one) (Additive II), 5,6-(methylbenzothiazol-2-yl)diazenyl)-2-hydroxyphenyl)-1-(4-hydroxyphenyl) prop-2-en-1-one (Additive III), 5-6-methylbenzothiazol-2-yl) diazenyl)-2-hydroxyphenyl)-1-(4-methoxyphenyl)prop-2-en-1-one (Additive IV), 4-6-methylbenzothiazol-2-yl) diazenyl)-2-2-hydroxy-5-methylphenyl)imino)methyl)phenol(AdditiveV). 4-6-methylbenzothiazol-2-yl) diazenyl)-2-2-hydroxy-5-ethylphenyl)imino)methyl) phenol (AdditiveVI) and(1E)-N-(5-((6-methylbenzo [d] thiazol-2-yl)diazenyl)-2-hydroxybenzylidene)-N'-(4-chlorophenyl)formimidamide(AdditiveVII). The effects of these additives on flammability of some of the thermosetting polymers (unsaturated polyester and epoxy resins), have been studied. Sheets of the specimens (resins with different weight percentages of additives), in dimensions (150X150X3) mm were prepared. Two standard test methods used to measured the flame retardation which are: (ASTM: D-2863) and (ASTM: D-635). Results are obtained from these tests indicated that, additive 6B has high efficiency as flame retardant, self–extinguishing (S.E.) at the percentage (0.1 %) for unsaturated polyester and the epoxy resins. Also self- extinguishing (S.E.) at the percentage (0.1%) for additives 1B, 4B and 5B,  in unsaturated polyester resin and non-burning occurs in 0.15% with Additive 6B and 5B in unsaturated polyester resin but it is occur in 0.2% with additives 6B and 5B in epoxy resin. Additive B shows low effect on flammability in both resins.Keywords: Flame retardant, Flammability, Polyester resin, Unsaturated polyester resin, Epoxy resin, Schiff base, Chalcones, Synthesis of shiff base, Identification of shiff base, Synthesis of chalcone, Identification of chalcone.